Destiny gate (2023) ebook - Cady, Ryan (Destiny Gate (2023), 2024)
During the Great Depression, Mitchell Slate did everything he could for his family. One day, his ride home takes a dark turn when Mitchell's train veers off the rails and into a macabre journey through his own fragile soul. There, he'll have to face that life is, for the most part, a product of the decisions you make, and for some, a "wrong" decision or two (or more) leads to a crossroads on the other side of the Destiny Gate. Can Mitchell fight for a chance to survive and start anew, or will he succumb to his inner demons and end it all for himself, or worse—those he loves?Writer RYAN CADY (HAUNT YOU TO THE END, Batman) and artist CHRISTIAN DiBARI (REVOLVERS, MAGDALENA: REFORMATION) take you on a mind-bending journey through the fabric of reality that will test Mitchell Slate's beliefs, his devotion to his family—and his sanity. Collects DESTINY GATE #1-4